Static Simulation on Speed bumps Made of Foam Concrete Foam with Durian Skin Fibers Using Ansys Software - Maraghi Muttaqin (Journal of Mechanical Engineering, Science, and Innovation, 2022)
Motorcyclists find speed bumps problematic because they require them to slow down. A concept comes to create a technology and can use a power plant with a generator driving source from speed bumps in its application. The product is designed and made on a big scale to allow all cars going through speed bumps. Because it is important to handle the kinetic energy generated from the vehicle in order for it to be transformed into electricity and connected to the load. Several tests, such as static and impact testing, are performed on the speed bump to get a material that is resistant to structural integrity. Simulation was used to perform static and impact testing using ansys software. As for the material, durian skin is very suitable as a mixture of materials, because it contains fibers that can be used for concrete reinforcement. Also obtained the equivalent stress of 0.05 MPa. The x-Axis voltage is 0.01MPa. The y-axis stress is 0.04 MPa. The results of this study can be concluded that the concrete composite reinforced with durian skin fiber also has the potential to be used as a speed bump power generator.